The perceptions and the practices of folk medicines among youths in Pakistan - Rani, Samina; Rehman, Adeela; Mohamad Diah, Nurazzura (Universiti Putra Malaysia, 2017)
The study aims to explore the relationship between the perceptions and the practices of folk medicines among youths in Pakistan. The quantitative research method was adopted to achieve its objectives. Structured questionnaires were distributed to respondents to collect data. The respondents are youths whose ages ranged from 18 to 25 years and they resided in the twin cities of Rawalpindi and Islamabad in Pakistan. The data were analysed using the Statistical Analysis Package of Social Sciences (SPSS version 13). The result shows that Pakistan youths have limited knowledge of folk medicines, and do not have a positive perception of it. A majority of them know the importance and usage of folk medicine but do not know how to prepare it and where to get it. Findings show that a lack of educational awareness about folk medicines has a strong impact on folk medicine practices. Pakistani youths mostly prefer medically specialised doctors compared to those who practise folk medicine, which they perceive to be slow in curing illnesses. It is recommended that folk wisdom about traditional healing practices be transferred to the next generation by their elders as well as via education-based awareness campaigns.